Analysis of under-deck cable stayed bridge and combined cable stayed bridge - Ahmad Zakwan, Zulkefly (2015)
Under-deck cable stayed bridge and combined cable stayed bridge is an unconventional cable bridge system which is instead of having cable stay above the deck like the conventional cable stayed system, the stays locates below the deck connected with the struts that as a pylon to the cable. In combined cable stayed system cable are both above and below the deck which like a mixing of conventional and unconventional design. The Purpose of this research is to study the principal theory of under deck cable stayed and combined cable stayed system and analyses the behavior of the system and compared with the conventional cable stayed system. In this research 2D static analysis of highway bridge have been investigated to determine the maximum and minimum stress on cable and deck, resultant moment and deflection of the bridge. Five model of the bridge with single and multiple spans are considered in this research which are the conventional design, Under-deck cable stayed, Intradosed, Combined cable stayed and Extradosed-intradosed design. The research intended to analyses the effect of the location of the cable stays to the overall behavior of the bridge. The manipulated variable in this analysis shows that cable stay above the deck produced better result than below the deck. But under-deck cable stayed system still produce an acceptable result that gives an option to the engineer. The analysis is successfully done using finite element software, LUSAS.